PENGARUH STRES KERJA DAN KOMITEMEN ORGANISASI TERHADAP TURNOVER INTENTION MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PT. INDOIL ENERGY - Arni Kurniati; Dewi Sartika Simbolon (Jurnal Manajemen FE-UB, 2019)
This type of research is a qualitative descriptive study, and data collection techniques usingthe method of literature study, field research that is interviews, documentation and includingquestionnaires. The author distributes questionnaires to the respondents of the companiesstudied, namely PT Indoil Energy employees as many as 100 respondents which is the number ofsamples in this study based on the Slovin formula.The research results obtained are job stress has a negative and significant influence on jobsatisfaction. The less work stress experienced by employees, the more positive attitudes arisingfrom employees include feelings and good emotional response behaviors to various aspects ofwork so that employees feel satisfaction at work; Organizational commitment has a positiveinfluence on job satisfaction. The higher organizational commitment that employees have, jobsatisfaction will also increase; Job stress has a positive and significant effect on TurnoverIntention. The more work stress experienced by Indoil Energy employees can be minimized, thelower the employee's intention to change jobs or find work in another organization;Organizational commitment has a negative and significant influence on Turnover Intention. Thehigher the Organizational Commitment felt by PT Indoil Energy employees, the lower theemployee's intention to change jobs or find work in another organization or the more employeeswant to remain in this organization.Job satisfaction felt by PT Indoil Energy employees has a negative and significant impacton Turnover Intention. Which means the more job satisfaction felt by employees, the TurnoverIntention will also decrease; Job stress has a positive and significant influence on turnoverintention through job satisfaction. The higher the work stress, the more dissatisfied the employeeis at work, so the intention to change work will increase and organizational commitment has anegative and significant influence on turnover intention through job satisfaction. The higherorganizational commitment that employees have, the more satisfied employees are at work so theintention to change jobs will decrease.Suggestions for companies that can be given in this study are management, especially in theleadership, to be able to sort out and adjust the tasks employed by employees in accordance withtheir respective job-desks in order to minimize the task pressure that is too much. PT IndoiilEnergy's management further increases trust in employees with a variety of policies that in thiscompany employees can grow and develop so that employees feel to be part of this companyand the management of PT Indoil Energy to better appreciate and provide work that isincreasingly honing the ability of employees by paying attention to the pressure so that employeescan feel proud and confident about their work. And for further researchers, it is hoped that theresults of this study will be used as a reference for further researchers for others who have beenused in this studyKeywords: Job Stress, Organizational Commitment, Job Satisfaction, and Turnover Intention